BENTUK PENGELOLAAN OBJEK WISATA ALAM PANTAI LINTUI NEGERI KOBI KABUPATEN MALUKU TENGAH - Laila, Nur; Lelloltery, Henderina; Iskar, Iskar (MARSEGU : Jurnal Sains dan Teknologi, 2024)
In managing ecotourism, the involvement of local communities in participating activities is very important. The aim of this research is to determine the forms of community-based ecotourism management at the Lintui Beach Natural Tourism Object (OWA). The method used is a survey method where data is obtained by interviewing or filling in a list of questions, direct observation and literature study. The research results show that the form of ecotourism management at OWA Lintui Beach includes; involved in maintaining the cleanliness of the beach (83.33%), involved in arranging opening and closing times for visits (63.33%), involved in determining entrance ticket prices (50%), providing facilities (76.67%), repairing damaged facilities ( 66.66%) and plans to build footpaths (66.66%), as well as involving BUMNeg to provide facilities for food and visitor needs as well as tour guide services.